2021
DOI: 10.14202/ijoh.2021.142-150
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, resistance to antimicrobials, and antibiotypes of Arcobacter species recovered from retail meat in Wasit marketplaces in Iraq

Abstract: Background and Aim: Arcobacter is a food-borne pathogen associated with human and animal infections. In Iraq, these infections and their adverse effects on public health have not been well investigated. For this reason, as well as to submit data on the resistance to antimicrobials and antibiotypes of the Arcobacter spp. and their occurrence in retail meat in the Wasit marketplaces, this study was undertaken. Materials and Methods: A total of 83 samples of fresh raw (n=35) and chilled meat (n=48) were purchase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 46 publications
(71 reference statements)
0
8
0
Order By: Relevance
“…The previous studies in Iraq confirmed this relationship by investigating the MDR phenomenon in many foodborne pathogens [ 21 , 48 – 51 ]. Other studies in Iraq also pointed to wrong practices regarding the abuse and misuse of antibiotics, which drove the exacerbation of this phenomenon [ 52 54 ]. Accordingly, these results highlighted the importance of preventing antibiotic overuse in reducing the MDR of Salmonella spp.…”
Section: Discussionmentioning
confidence: 99%
“…The previous studies in Iraq confirmed this relationship by investigating the MDR phenomenon in many foodborne pathogens [ 21 , 48 – 51 ]. Other studies in Iraq also pointed to wrong practices regarding the abuse and misuse of antibiotics, which drove the exacerbation of this phenomenon [ 52 54 ]. Accordingly, these results highlighted the importance of preventing antibiotic overuse in reducing the MDR of Salmonella spp.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the prevalence of these diseases, there has been a push for developing better sterilizing techniques for meat [18]. In Iraq, there is not as much research on C. jejuni infections as there is on other foodborne bacteria [19][20][21][22][23]. Therefore, there is an urgent need to conduct more studies on this pathogen, especially due to the large consumption of poultry meat, which is the primary source of campylobacteriosis.…”
Section: Introductionmentioning
confidence: 99%
“…The mindset of those who work with food also influences how they do their jobs [8]. Multiple investigations conducted in Iraq have found evidence of food contamination with dangerous FBDs [22][23][24][25][26][27][28][29][30][31][32][33][34][35][36]. As workers in the food industry play a crucial role in food contamination and FBDs, studying the KAP of food safety among this population is important.…”
Section: Introductionmentioning
confidence: 99%